Comparison of Three Methods Used in the Diagnosis of Extraesophageal Reflux in Children with Chronic Otitis Media with Effusion - Formánek, Martin; Komínek, Pavel; Matoušek, Petr; Tomanova, Radoslava; Urban, Ondřej; Zeleník, Karol (Gastroenterology research and practice, 2015)
Objectives. Detection of extraesophageal reflux (EER) in children with chronic otitis media with effusion (OME) using three different diagnostic methods. Methods. Children between 1 and 7 years with OME who underwent adenoidectomy and myringotomy with insertion of a ventilation tube were included in this prospective study. EER was detected using three methods: oropharyngeal pH was monitored for 24 hours using the Restech system; detection of pepsin in middle ear fluid obtained during myringotomy was done using Peptest, and detection of pepsin in an adenoid specimen was done immunohistochemically. Results. Altogether 21 children were included in the study. Pathological oropharyngeal pH was confirmed in 13/21 (61.9%) children. Pepsin in the middle ear fluid was present in 5/21 (23.8%) children; these 5 patients were diagnosed with the most severe EER established through monitoring of oropharyngeal pH. No specimen of adenoids tested was positive for pepsin upon immunohistochemical examination. Conclusions. Diagnosis of EER in patients with OME using Restech is sensitive but less specific when compared to the detection of pepsin in middle ear fluid using Peptest. Pepsin in the middle ear was consistently present in patients with RYAN score above 200, and these patients in particular could potentially profit from antireflux therapy.